1995
DOI: 10.2307/2154771
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Viscous Solutions for Systems of Conservation Laws

Abstract: Abstract.We exhibit an example of mechanism responsible for multiple solutions in the Riemann problem for a mixed elliptic-hyperbolic type system of two quadratic polynomial conservation laws. In this example, multiple solutions result from folds in the set of Riemann solutions. The multiple solutions occur despite the fact that they all satisfy the viscous profile entropy criterion. The failure of this criterion to provide uniqueness is evidence in support of a need for conceptual change in the theory of shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Other authors have made the point that loss of hyperbolicity causes severe difficulties; see Azevedo and Marchesin (1995); Azevedo et al (1996Azevedo et al ( , 1999Azevedo et al ( , 2002; Bell et al (1986);Čanić (2003); Frid and Liu (1998). The difficulties entailed by loss of hyperbolicity have been mentioned as supporting Juanes and Patzek's model.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other authors have made the point that loss of hyperbolicity causes severe difficulties; see Azevedo and Marchesin (1995); Azevedo et al (1996Azevedo et al ( , 1999Azevedo et al ( , 2002; Bell et al (1986);Čanić (2003); Frid and Liu (1998). The difficulties entailed by loss of hyperbolicity have been mentioned as supporting Juanes and Patzek's model.…”
Section: Discussionmentioning
confidence: 96%
“…Our conclusions do not contradict Bell et al (1986), as these authors deliberately chose parameters in Stone's model that maximize the size of the elliptic region. All the strange phenomena observed by many authors (see Holden (1987); Azevedo and Marchesin (1995); Azevedo et al (1996Azevedo et al ( , 1999Azevedo et al ( , 2002; Bell et al (1986);Čanić (2003); Frid and Liu (1998)) occur in an area about 10 −3 of the saturation triangle. In Fig.…”
Section: Comparison Between the Models Of Corey And Of Stonementioning
confidence: 92%
“…2. In three-phase, immiscible flow the loss of hyperbolicity may cause nonunique solutions (Azevedo and Marchesin 1995;Azevedo et al 1996). When umbilic points are present, it is necessary to introduce transitional waves that do not meet Lax and Liu entropy conditions in order to construct solutions (Lax 1957;Isaacson et al 1990;Schecter et al 1996).…”
Section: Loss Of Hyperbolicitymentioning
confidence: 99%
“…As a consequence, the eigenvalues of Eq. 11 may become complex conjugates (Azevedo and Marchesin 1995;Azevedo et al 1996;Falls and Schulte 1992a, b;Guzman and Fayers 1997a, b). This would result in two complex and one real characteristic.…”
Section: Loss Of Hyperbolicitymentioning
confidence: 99%
“…In threephase immiscible flow it has been shown that it is not always possible to construct solutions to Riemann problems using Lax entropy constraints (Azevedo and Marchesin 1995;Azevedo et al 1996;Isaacson et al 1990;Marchesin et al 1997;Schecter et al 1996). A new entropy condition is necessary.…”
Section: Fast Slow and Transitional Shocksmentioning
confidence: 99%